(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the place of physical education and sport in student life as a multidimensional socio-pedagogical, health-promoting, and personality-forming process. The aim of the study is to provide a systematic account of how physical activity in higher education affects health, psycho-emotional stability, academic productivity, social integration, and future work capacity. The study relies on an integrative literature review, analysis of normative documents, and synthesis of recent international meta-analyses. The findings indicate that physical education and sport strengthen students’ functional health status, reduce stress and depressive symptoms, improve sleep quality, and foster universal competences such as self-regulation, discipline, time management, teamwork, and leadership. The positive relationship between regular physical activity and academic outcomes is substantiated, particularly through attention, executive functions, motivation, and persistence in study. At the same time, a digitalized lifestyle, prolonged sitting, heavy academic workload, insufficient sports infrastructure, and gender, economic, and motivational barriers were identified as major constraints on student participation. The article proposes scientific and practical recommendations for higher education institutions, including healthy campus policies, flexible sport programs synchronized with class schedules, inclusive participation mechanisms, monitoring systems, and movement-supportive learning environments. It is concluded that physical education and sport are not merely leisure activities but strategic determinants in shaping students as healthy, socially responsible, academically resilient, and competitive individuals.